0114 Video feedback and bookmarks. (2nd November 2015) - Gay, Christopher; Graby, Matthew; Charlton, Olivia; Raina, Anju; Jaworskagrajek, Malgorzata; Riby, Stuart
Abstract : Background/context: HILS have been using video debriefing in simulation since our centre opened, yet have noticed a variability of faculty success in using it. In an attempt to uncover best practise, the technical team set out to document the effective use of bookmarks in video debriefing during a 15 day mandatory simulation course for Junior Doctors. Description of innovation or topic: The Technical Team recorded the following: The number of total bookmarks made per scenario The number of bookmarks actually used in each debriefing Whether the use of the video bookmark was successful or not Comments on communication between technician and debriefer Improvements/outcomes (anticipated or recorded): With immediate effect, there were obvious techniques which resulted in differences between the debriefing of scenarios such as Whether bookmarks where identified with number, time or text description Whether bookmarks were used from printed paper or from onscreen menus When the data is analysed, we also expect to find An increase in the number of 'good' bookmarks used over time from individual debriefers No correlation between number of bookmarks made, and bookmarks used Take home messages: There are subtle improvements that can be made to improve the effectiveness of using video in a debriefing There is a wide variation in the use of video debriefing 1 Reference: http://icenetblog.royalcollege.ca/2015/02/10/effective-debriefing-tips-for-simulation-based-medical-education/